Cardiorespiratory fitness and sports activities in children and adolescents with solitary functioning kidney. Issue 1 (December 2016) - Tancredi, Giancarlo; Lambiase, Caterina; Favoriti, Alessandra; Ricupito, Francesca; Paoli, Sara; Duse, Marzia; De Castro, Giovanna; Zicari, Anna; Vitaliti, Giovanna; Falsaperla, Raffaele; Lubrano, Riccardo
Abstract Background An increasing number of children with chronic disease require a complete medical examination to be able to practice physical activity. Particularly children with solitary functioning kidney (SFK) need an accurate functional evaluation to perform sports activities safely. The aim of our study was to evaluate the influence of regular physical activity on the cardiorespiratory function of children with solitary functioning kidney. Method Twenty-nine patients with congenital SFK, mean age 13.9 ± 5.0 years, and 36 controls (C), mean age 13.8 ± 3.7 years, underwent a cardiorespiratory assessment with spirometry and maximal cardiopulmonary exercise testing. All subjects were divided in two groups: sedentary (S) and trained (T) patients, by means of a standardized questionnaire about their weekly physical activity. Results We found that mean values of maximal oxygen consumption (VO2 max) and exercise time (ET) were higher in T subjects than in S subjects. Particularly SFK-T presented mean values of VO2 max similar to C-T and significantly higher than C-S (SFK-T: 44.7 ± 6.3 vs C-S: 37.8 ± 3.7 ml/min/kg;p  < 0.0008). We also found significantly higher mean values of ET (minutes) in minutes in SFK-T than C-S subjects (SFK-T: 12.9 ± 1.6 vs C-S: 10.8 ± 2.5 min;p <0.02). Conclusion Our study showed that regular moderate/high level of physical activity improve aerobic capacity (VO2 max) and exercise tolerance in congenital SFK patients without increasing the risks for cardiovascular accidents and accordingly sports activities should be strongly encouraged in SFK patients to maximize health benefits.